Exploring the development of judgement and decision making in 'competent' outdoor instructors. Issue 1 (2nd January 2022) - Mees, Alice; Toering, Tynke; Collins, Loel
ABSTRACT: Over the last ten years there has been growing interest in the judgement and decision making (JDM) of outdoor professionals, though research to date has focused on the JDM processes of experts. In contrast, this study examined the JDM of less experienced, competent, but fully qualified outdoor instructors (N = 9) and the development of their JDM skills. Using semi-structured interviews and thematic analysis, we identified two overarching themes: Firstly, managing the cognitive load (relating to instructor JDM), and secondly social experiential learning (relating to instructor JDM development). We found these outdoor instructors needed to manage complex situational demands and high cognitive loads, while balancing the safety of their group with the development of their own JDM. We propose that a combination of challenging formative experiences, community of practice interactions, and explicit development of metacognition are essential to outdoor instructors JDM development. Implications for training, and future research are discussed.